Web‐based self‐monitoring for weight loss among overweight/obese women at increased risk for breast cancer: the HELP pilot study. Issue 8 (27th November 2012) - Cadmus‐Bertram, Lisa; Wang, Julie B.; Patterson, Ruth E.; Newman, Vicky A.; Parker, Barbara A.; Pierce, John P.
Abstract: Objective: Excess weight and physical inactivity are modifiable risk factors for breast cancer. Training women to use self‐help resources over the internet has potential for reducing intervention costs and enhancing maintenance. Methods: A total of 50 overweight/obese women at increased breast cancer risk were randomized to a 12‐week intervention or a comparison group. Telephone‐based sessions trained participants to use web‐based self‐monitoring tools to set goals and track diet and exercise. The comparison group received dietary information but no training. At baseline and 12 weeks, participants were weighed and wore an accelerometer. Results: Participants were aged 60.9 ± 0.8 years with a BMI of 33.1 ± 0.6 kg/m 2 . The intervention group lost 3.3 ± 4.0 kg, whereas the comparison group gained 0.9 ± 3.4 kg ( p < 0.0001). Intervention participants who found the website helpful lost 5.6 ± 0.7 kg; those who did not lost 0.8 ± 0.9 kg ( p < 0.001). Change in physical activity was +70 ± 140 min/week among those who found the website helpful, −6 ± 75 min/week among those who did not, and −34 ± 207 min/week in the comparison group ( p < 0.01). Conclusions: A program to train women to use web‐based weight loss tools achieved a substantial short‐term weight loss among the majority of participants. Further follow‐up is needed to assess weight loss maintenance over time. Copyright © 2012 John Wiley & Sons, Ltd.